1968
DOI: 10.1085/jgp.52.1.144
|View full text |Cite
|
Sign up to set email alerts
|

Alteration by Xylocaine (Lidocaine) and Its Derivatives of the Time Course of the End Plate Potential

Abstract: A BSTRACT Xylocaine and its derivatives act specifically at the neuromuscular junction within the concentration range 0.05 to 2.0 m. The charged form is the active form of the drugs. There is no correlation between "local anesthetic" activity and effect at the junction. Like d-tubocurarine, these drugs have little or no effect on quantum content, acetylcholinesterase activity, or the passive impedance of the muscle fiber. Yet they produce end plate potentials characterized by a brief, early component and a lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
68
1
1

Year Published

1977
1977
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(79 citation statements)
references
References 19 publications
9
68
1
1
Order By: Relevance
“…Athird mechanism by which local anaesthetics could interact with the ACh receptor is by perturbing the electric field in its vicinity. Steinbach (1968 a) demonstrated that the charged form of the local anaesthetics are responsible for altering e.p.c.s. The charged local anaesthetic molecules appear to bind to acidic phospholipids (Skou, 1954;Shanes & Gershfield, 1960;Ohki, 1970;Papahadjopoulos, 1970;Muller & Finkelstein, 1972;Seeman, 1972, Papahadjopoulos, Jacobsen, Poste & Shepard 1975, and thereby change the membrane surface electrical potential (Muller & Finkelstein, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Athird mechanism by which local anaesthetics could interact with the ACh receptor is by perturbing the electric field in its vicinity. Steinbach (1968 a) demonstrated that the charged form of the local anaesthetics are responsible for altering e.p.c.s. The charged local anaesthetic molecules appear to bind to acidic phospholipids (Skou, 1954;Shanes & Gershfield, 1960;Ohki, 1970;Papahadjopoulos, 1970;Muller & Finkelstein, 1972;Seeman, 1972, Papahadjopoulos, Jacobsen, Poste & Shepard 1975, and thereby change the membrane surface electrical potential (Muller & Finkelstein, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…The site to which local anaesthetics (quinacrine included) bind on the receptor-rich membrane fragments is distinct from the receptor site for agonists [19]. It is probably functionally related to and possibly located on the ion-translocating device, or ionophore [28,29]. The failure to recover both the effect of local anesthetics on the affinity increase caused by agonists and the slow response monitored by quinacrine may explain the variable success of the attempts to 'reconstitute' the permeability response to cholinergic agonists.…”
Section: Discussionmentioning
confidence: 99%
“…1974;Seyama & *Narahashi, 1975;Torda & Gage, 1976) and to increase the quantal content of end plate potentials (e.p.ps) (Thompson & Turkanis, 1973). In its cardiac antiarrhythmic effect, it resembles lignocaine which also affects the time course of endplate currents (Steinbach, 1968;Ruff, 1976). We have therefore investigated the effect of phenytoin sodium on synaptic transmission at the mammalian endplate.…”
Section: Introductionmentioning
confidence: 99%